'Just transition'? Conceptual challenges meet stark reality in a 'transitioning' coal region in Australia. Issue 4 (7th June 2018) - Snell, Darryn
ABSTRACT: 'Just transition' (JT) is an increasingly popular concept developed by unions and adopted and adapted by academics, environmentalists, government and non-governmental organizations, and international institutions in recognition of the need to address social concerns and inequities emerging from efforts to address environmental problems. It has been noted, however, that 'JT' lacks both conceptual clarity and empirical evidence of its practical applications. This paper examines the 'theory' and practice of 'JT' by first considering the competing interpretations and conceptual understandings of 'JT' and second, the challenges of realizing a 'JT' in an Australian coal region where transition is occurring. The paper argues that achieving 'JT' requires more than government provisions and interventions and that unions must perform an active part in the 'JT' process through their relations with employers, workers, government, and community. It suggests the lack of clarity within the 'JT' literature may be the concept's lasting strength.